Predicted distribution of the masked palm civet Paguma larvata (Mammalia: Carnivora: Viverridae) on Borneo - Semiadi, G; Ross, J; Hearn, AJ; Macdonald, DW; Mathai, J; Augeri, DM; Fredriksson, G; Rustam; Alfred, R; Hall, J; Heydon, M; Brodie, JF; et al. (Lee Kong Chian Natural History Museum, 2016)
The masked palm civet Paguma larvata is a small carnivore within the civet family Viverridae, currently listed as Least Concern on The IUCN Red List of Threatened Species. Across its global range the masked palm civet uses a range of habitats in tropical and subtropical regions, from lowlands to highlands, but its exact ecological requirements and the use of modified habitat remains unclear. We analysed 49 (Balanced Model) and 72 (Spatial Filtering Model) location records of the masked palm civet from Borneo to predict habitat suitability. The resulting model predicted the interior and high elevation areas of Borneo to be suitable habitat, while the coastal and other low-lying areas, such as the extensive peat swamp forests in Central Kalimantan, were predicted to be unsuitable. Greater survey effort in South, Central and West Kalimantan and in Brunei is necessary to obtain more records to improve current models and understanding. The species is probably widespread in Borneo and its likely stronghold is in the higher-elevation forests which are currently less threatened and for a large part protected. Thus, speciesspecific conservation efforts are not considered warranted at this time.